Anti-Stereotypical Portrayal of Women in The Shadow of the Crescent Moon - Oroosa Anwar (Journal of Religion and Society, 2025)
Fatima Bhutto's novel The Shadow of the Crescent Moon vividly portrays the conflict-ridden town of Mir Ali, marked by terrorism, injustice, fear, and deprivation of basic rights. Amid this backdrop of misery and isolation, the novel challenges traditional gender stereotypes that depict women as submissive, weak, dependent, emotionally fragile, and inferior to men, while men are seen as courageous, independent, and dominant. This study employs a qualitative research design rooted in feminist literary criticism, drawing on Lois Tyson's (2006) framework to interrogate patriarchal gender roles and Patricia Hill Collins' (2004) Matrix of Domination to examine intersecting oppressions of gender, class, ethnicity, and conflict. Through close textual analysis delimited to the characters of Samarra and Mina, the study demonstrates how Bhutto subverts conventional gender roles. Samarra, introduced as a tomboyish girl who engages in activities typically reserved for males such as playing cricket, riding horses, shooting pellet guns, and motorbikes, exhibits remarkable bravery and independence. Despite abandonment by her father and lover Aman Erum, denial of education, and brutal kidnapping and torture, Samarra refuses to succumb. She remains silent during abduction, confronts her torturers defiantly, and transforms into a resilient rebel, leading a secret plot against authority, defying societal norms by smoking publicly and rejecting veils. Similarly, Mina, a psychology lecturer shattered by the terrorist killing of her son Zalan, evolves from grief-stricken withdrawal to fierce confrontation. In a life-threatening encounter with Taliban militants, while her husband Sikandar cowers, lies, and begs for mercy, Mina boldly reveals her faith, physically attacks the armed men, and vociferously condemns them for their injustices, invoking her son's innocent death. Through these portrayals, Bhutto illustrates women as courageous, determined, and capable of enduring and resisting oppression more effectively than men, negating stereotypes and highlighting female agency in a patriarchal, war-torn society. Keywords: Fatima Bhutto, Shadow of the Crescent Moon, Gender stereotypes, Women empowerment, Samarra, Courage